Blood–Brain Barrier Remodeling in an Organ‐on‐a‐Chip Device Showing Dkk1 to be a Regulator of Early Metastasis. Issue 4 (5th February 2023) - Westerhof, Trisha M.; Yang, Benjamin A.; Merill, Nathan M.; Yates, Joel A.; Altemus, Megan; Russell, Liam; Miller, Anna J.; Bao, Liwei; Wu, Zhifen; Ulintz, Peter J.; Aguilar, Carlos A.; Morikawa, Aki; et al.
Abstract : Brain metastases are the most lethal progression events, in part because the biological processes underpinning brain metastases are poorly understood. There is a paucity of realistic models of metastasis, as current in vivo murine models are slow to manifest metastasis. Metabolic and secretory modulators of brain metastases utilizing two models consisting of in vitro microfluidic devices are delineated: 1) a blood–brain niche (BBN) chip that recapitulates the blood–brain‐ barrier and niche; and 2) a migration chip that assesses cell migration. Secretory cues provided by the brain niche that attract metastatic cancer cells to colonize the brain niche region are reported. Astrocytic Dkk‐1 is increased in response to brain‐seeking breast cancer cells and stimulates cancer cell migration. Brain metastatic cancer cells under Dkk‐1 stimulation increase gene expression of FGF‐13 and PLCB1. Further, extracellular Dkk‐1 modulates cancer cell migration upon entering the brain niche. Abstract : Culture in a synthetic blood–brain barrier reveals the tumor microenvironment remodels differentially based on metastatic nature of the tumor cells. Moreover, analysis of the secretions, genes, and pathways involved identifies Dkk1 as promoting remodeling of the prometastatic brain niche. Treatment with Dkk1 antibodies and FGF13 knockdowns confirms its role.